2001
DOI: 10.1002/path.1005
|View full text |Cite
|
Sign up to set email alerts
|

Low incidence of SV40‐like sequences in ependymal tumours

Abstract: Between 1955 and 1963, millions of children and adults were exposed to SV40-contaminated poliovirus vaccines. The oncogenic potential of this polyomavirus was revealed when intracerebral inoculation of SV40 into newborn hamsters resulted in the development of ependymomas and choroid plexus papillomas. Subsequently, SV40-like sequences were repeatedly detected in human ependymomas with broadly ranging incidence rates of 7-90%. Most epidemiological studies, however, have not described an increased occurrence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…However, one sample set was re-evaluated using 1 g DNA [40], and this did not result in improved detection of SV40 [24]. In conventional PCR, the inclusion of 1 g DNA did not always warrant positive findings [10,18], while smaller DNA inputs did not necessarily lead to negative results [11], in particular with low quality DNA from paraffin-embedded tissue [16,19,20,41]. It should also be noted that amplification of non-specific bands has been reported for commonly used SV40 primers with DNA inputs above 250 ng [10].…”
Section: Discussionmentioning
confidence: 99%
“…However, one sample set was re-evaluated using 1 g DNA [40], and this did not result in improved detection of SV40 [24]. In conventional PCR, the inclusion of 1 g DNA did not always warrant positive findings [10,18], while smaller DNA inputs did not necessarily lead to negative results [11], in particular with low quality DNA from paraffin-embedded tissue [16,19,20,41]. It should also be noted that amplification of non-specific bands has been reported for commonly used SV40 primers with DNA inputs above 250 ng [10].…”
Section: Discussionmentioning
confidence: 99%
“…In our study and the Austrian study, 10 all of the specimens were fixed in formalin, which could have degraded the DNA. However, few tumors in the German studies were SV40 ϩ , despite use of fresh frozen specimens, 9,11 and other studies using only formalin-fixed tissues yielded positive results. 7,26 Our quantitative testing for the human gene GAPDH indicated that most of our specimens had adequate PCR-amplifiable DNA.…”
Section: Discussionmentioning
confidence: 99%
“…The set of primers RA1 (nt 266-245) and RA2 (nt 5,195-5,218) targets the SV40 regulatory region; it allows the distinction between archetypal SV40 strains containing, only a 72-bp insert motif (expected size of PCR product 242 bp), and laboratory-adapted SV40 strains, with duplicated 72-bp insert sequence (expected size of PCR product 314 bp) [46,47]. The set of primers LA1 (nt 2,251-2,274) and LA2 (nt 2,545-2,522) amplify a 294-bp sequence in the VP1 gene encoding the major capsid protein of the virus.…”
Section: Dna Extractionmentioning
confidence: 99%